COMPUTATIONAL LINGUISTICS: a bibliographic mapping from 2000 to 2020 - Oliveira, Anne Cleres da Silva; Freschi, Ana Carolina (Revista Interface Tecnológica, 2020)
Computational Linguistics is a multidisciplinary field that involves Artificial Intelligence, Informatics, and Linguistics. This area seeks to develop, through logical-formal modeling, systems with the capacity to recognize and produce information presented by natural language. The objective of this work, based on exploratory bibliographic research, is to present a bibliographic mapping of studies involving Computational Linguistics between 2000 and 2020 to recognize its diverse applications. This investigation is justified by the very importance of this research field for new technologies development and by the knowledge of possible areas in which it can be used. In the analysis, it was found other areas related to Computational Linguistics and how they are interconnected in the construction of new tools. Therefore, this investigation shows a clear understanding of its origin and usability in the processes of systems creation related to human language manipulation.